Application of the Reverse Line Blot Assay for the Molecular Detection of Theileria and Babesia sp in Sheep and Goat Blood Samples from Pakistan - Iqbal, F.; Khattak, R. M.; Ozubek, S.; Khattak, M. N. K.; Rasul, A.; Aktas, M. (Iranian Scientific Society Medical Entomology, 2013)
Background: The present study was designed to detect the presence of tick-borne parasites (Theileria and Babesia spp.) in 196 blood samples collected from apparently healthy sheep and goats from two provinces, Punjab and Khyber Pukhtoon Khwa, in Pakistan. Methods: Reverse line blot (RLB) assay was applied for the parasitic detection by the amplification of hypervariable V4 region of the 18S ribosomal RNA (rRNA) gene. A membrane with covalently linked generic and species specific oligonucleotide probes was used for the hybridization of amplified PCR products. Results: Parasites were detected in 16% of the ruminant blood samples under study. Two Theileria species, T. lestoquardi and T. ovis, were identified in samples. 25, of the total 32, infected animals were from Khyber Pukhtoon Khwa. Conclusion: Sheep were more prone to tick borne haemoprotozans as 81% infected samples were sheep as compared to 19% goats (P > 0.001). Risk factor analysis revealed that male (P = 0.03), animals infested by ticks (P = 0.03) and herd composed of sheep only (P = 0.001) were more infected by blood parasites.
Keywords: Sheep; Goat; Theileria; Babesia; 18S rRNA gene; RLB